KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 1 SULIKI PADA PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CORE DENGAN BANTUAN LIVE WORKSHEET - Alhafizah, Nurul (Departemen Matematika, 2024)
Improving students' mathematical communication skills is an important goal in the field of mathematics education that they must achieve. The mathematical communication skills of class XI at SMA Negeri 1 Suliki are currently at a poor level. One potential solution to this problem is to implement a cooperative learning model of Connecting, Organizing, Reflecting, and Extending (CORE) type, which is integrated with student worksheets (LKS) as a tool in the learning process. This study seeks to determine whether students who apply the CORE type cooperative learning model equipped with LKS have better mathematical communication compared to the implementation of the direct learning model. For the purpose of this investigation, a quasi-experimental methodology known as the Nonequivalent Posttest-Only Control Group approach was used. For the purpose of this study, the population consisted of all learners enrolled in eleventh grade at SMA Negeri 1 Suliki during the 2023/2024 school year. Classes XI F 1 and XI F 4 were selected as sample classes. The final test of mathematical communication ability was used as a measuring tool for the purpose of this study. The data results were then tested by t-test, and the P-value obtained from the analysis was 0.023. Since the p-value is lower than 0.05, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is adopted instead. Therefore, it can be concluded that the implementation of the LKS-assisted learning model with the CORE (Connecting, Organizing, Reflecting, and Extending) approach is superior in terms of mathematical communication skills when compared to the direct learning model.Keywords– Connecting, organizing, reflecting, extending models, live worksheet, mathematical communication skills